1996
DOI: 10.1021/bp960027f
|View full text |Cite
|
Sign up to set email alerts
|

α-Ketoglutarate Assay Based on Fluorescence Quenching by NADH

Abstract: A new assay procedure for the measurement of ketoglutarate concentrations is described which is based on substrate-induced quenching (SIQ) of a fluorophore. The method makes use of the photoreaction between a fluorophore (thionine) and NADH. The latter is consumed during an enzymatic reaction between ketoglutarate and L-glutamic dehydrogenase. The conversion yield of cofactor from its reduced form to oxidized forms represented as an overall change in the population of the excited state population of the fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…31 The authors describe this as "substrate-induced quenching" (SIQ) based on a light-induced redox reaction. We intend to present a more detailed analysis and possible applications of this method in a separate publication.…”
Section: Brightness Change Due To Quenching By a Small Molecule Analytementioning
confidence: 99%
See 1 more Smart Citation
“…31 The authors describe this as "substrate-induced quenching" (SIQ) based on a light-induced redox reaction. We intend to present a more detailed analysis and possible applications of this method in a separate publication.…”
Section: Brightness Change Due To Quenching By a Small Molecule Analytementioning
confidence: 99%
“…After completing the experiments reported here, we found that a similar phenomenon as the NADH-and light-dependent quenching of resorufin has been reported for the structurally related dye thionine. 31 The authors describe this as "substrate-induced quenching" (SIQ) based on a light-induced redox reaction. We intend to present a more detailed analysis and possible applications of this method in a separate publication.…”
Section: Brightness Change Due To Quenching By a Small Molecule Analytementioning
confidence: 99%
“…However, data reported elsewhere by us and by Sharma have verified that the reaction product of excited thionine and NADH and NADPH is NAD + and NADP + , respectively, by its ability to act as an electron acceptor in NAD + or NADP + specific enzyme reactions. [35][36][37] These results indicate that the quenching of thionine is at least partially due to an excited-state redox process that results in a net electron transfer from NADH or NADPH to thionine.…”
Section: Reaction Mechanismmentioning
confidence: 86%
“…Consequently, this method was applied to measure ethanol 3 and glucose levels 7 and to monitor the activity of α-ketoglutarate. 8 However, the method had not been used in miniaturized, HTScompatible format.…”
Section: Introductionmentioning
confidence: 99%